William Michelsen: Den sælsomme forvandling i N. F. S. Grundtvigs liv - Grønbæk, Villiam (Grundtvig-studier, 1956)
William Michelsen: The strange Metarphosis in N. F. S. Grundtvigs life, 1956, 288 pages. By Villiam Grønbæk. The title of Dr. Michelsen’s work, which forms a supplement to his thesis, “ Tilblivelsen af Grundtvigs historiesyn” (“ The Origin of Grundtvig’s View of History”), is taken from the retrospective survey of his activety as a historian made by Grundtvig in 1833. In this Grundtvig states that his literary production is a reflection of his life. While Dr. Michelsen in his thesis showe the significance of Grundtvig’s reading as a child in influencing the development of his view of history in a Biblical direction, he here investigates the question as to whether the interpretation of Grundtvig’s view of history at which he arived in his thesis is in accordance with the facts which come to light in Grundtvig’s literary works and papers dating from the years 1808 to 1812 — that is, the years in which his first “ Verdenskrønike” (“ World Chronicle”) came out. Through the explanations of the author, which are based on the extensive use of printed and unprinted material and have nothing to do with speculation, we follow Grundtvig on his way to the Biblical view of history. The origin of Grundtvig’s view of history is set in its context in relation to his own human and religious development. Dr. Michelsen has given us the picture of Grundtvig’s personal and religious development in the years before the crisis on 1810—11 which we have long lacked. The author’s exceptionally fine qualities as a research worker have set their stamp upon the work.